Studying the processing of food dye from beet juice - Sheiko, Tamila; Tkachenko, Serhii; Mushtruk, Mikhailo; Vasyliv, Volodymyr; Deviatko, Olena; Mukoid, Roman; Bilko, Marina; Bondar, Nikolai (My University, 2019)
The manuscript describes a new method of red beet processing and the technology of manufacturing food colorant from the juice concentrate, which is natural, safe and useful analogue to existing expensive offers on the market of similar goods that have chemical origin not useful for regular consumption. Nowadays in order to give to food products a colour, close to natural coloring of fruits and vegetables, expensive synthetic dyes are used, which might have cancer-inducing effect when being accumulated by human organism. Therefore improving the technology for producing food grade dye from red beet juice is remarkably important task. Currently, there is a problem for vegetable processors – pectin substances complicate the process, like the illumination of juice and negatively affect its storage capacity. The article below reveals and substantiates the necessity of using a natural carbon-containing adsorbent shungite for the purification of beet juice from pectin substances. On the basis of the study, the authors suggest a more cost-effective way of producing a food dye from juice concentrate, which allows avoiding usage of expensive enzyme processing additives.
Keywords: food grade dye; red beet juice; shungite; барвник харчовий натуральний; сік буряка червоного; шунгіт; кафедра біотехнології продуктів бродіння і виноробства